Consequences of the Endogenous N-Glycosylation of Human Ribonuclease 1 - Ressler, Valerie T. (Biochemistry, 2019)
Ribonuclease 1 (RNase 1) is the most prevalent human homolog of the archetypal enzyme, RNase A. RNase 1 contains sequons for N-linked glycosylation at Asn34, Asn76, and Asn88 and is N-glycosylated at all three sites in vivo. The effect of N-glycosylation on the structure and function of RNase 1 is unknown. By using an engineered strain of the yeast Pichia pastoris, we installed a heptasaccharide (Man(5)GlcNAc(2)) on the side chain of Asn34, Asn76, and Asn88 to produce the authentic triglycosylated form of human RNase 1. As a glutamine residue is not a substrate for cellular oligosaccharyltransferase, we used strategic asparagine-to-glutamine substitutions to produce the three diglycosylated and three monoglycosylated forms of RNase 1. We found that the N-glycosylation of RNase 1 at any position attenuates its catalytic activity but enhances both its thermostability and its resistance to proteolysis. N-Glycosylation at Asn34 generates the most active and stable glycoforms, in accord with its sequon being highly conserved among vertebrate species. These data provide new insight on the biological role of the N-glycosylation of a human secretory enzyme.